Pemanfaatan Platform Digital Shopee Pada Tiktok Dan Brand Awareness Terhadap Keputusan Pembelian Di Shopee (Studi Kasus Komunitas Sepak Bola Didesa Srigading Lampung Timur) - Rahmad Saputra; Bambang Suhada; Fitriani (Universitas Muhammadiyah Metro, 2025)
The rapid progress of information technology today has made changes so quickly. Along with advances in business, internet technology can reach consumers, creating new opportunities for interaction and transactions. This research aims to find out whether the use of the TikTok digital platform and brand awareness influence purchasing decisions on Shopee e-commerce. In this research, researchers used quantitative research. The population in this study were members of the football community in Srigading village, East Lampung with a total of 41 respondents. Based on this research, because the population is not greater than 100 respondents, the author took 100% of the population in the soccer community of Srigading village, East Lampung, namely 41 respondents. The data collection technique used was using interviews and questionnaires. Data analysis used includes validity test, reliability test, normality test, linearity test, homogeneity test and partial test (T test) and simultaneous test (F test) with the help of the SPSS version 25.0 application. There is a positive and significant influence of the Shopee Digital Platform on Tiktok and Brand Awareness on Purchase Decisions on Shopee in the Football Community in Srigading Village, East Lampung.